Effects of Cognitive Training on Resting-State Functional Connectivity of Default Mode, Salience, and Central Executive Networks - Cao, Weifang; Cao, Xinyi; Hou, Changyue; Li, Ting; Cheng, Yan; Jiang, Lijuan; Luo, Cheng; Li, Chunbo; Yao, Dezhong (Frontiers in Aging Neuroscience, 2016)
Neuroimaging studies have documented that ageing can disrupt certain higher cognitive systems such as the default mode network (DMN), the salience network (SN) and the central executive network (CEN). The effect of cognitive training on higher cognitive systems remains unclear. This study used a one-year longitudinal design to explore the cognitive training effect on three higher cognitive networks in healthy older adults. The community-living healthy older adults were divided into two groups: the multi-domain cognitive training group (24 sessions of cognitive training over a three-month period) and the wait-list control group. All subjects underwent cognitive measurements and resting-state functional magnetic resonance imaging (fMRI) scanning at baseline and at one year after the training ended. We examined training-related changes in functional connectivity (FC) within and between three networks. Compared with the baseline, we observed maintained or increased FC within all three networks after training. The scans after training also showed maintained anti-correlation of FC between the DMN and CEN compared to the baseline. These findings demonstrated that cognitive training maintained or improved the functional integration within networks and the coupling between the DMN and CEN in older adults. Our findings suggested that multi-domain cognitive training can mitigate the ageing-related dysfunction of higher cognitive networks.